Ekpolorasi Hombo Batu Terhadap Pembelajaran Matematika - Sentosa Giawa; Hardi Tambunan (Journal on Education, 2024)
This research aims to explore the stages of Homo Batu culture towards school mathematics learning. This research was conducted in South Nias, North Sumatra Province. The type of research is ethnomathematics, namely analysis of the stages carried out by a fahombo. The research instrument uses interview and observation sheets. Qualitative data analysis is used to explore the stages carried out by a fahombo in learning mathematics. Based on the results of exploration and analysis, it can be concluded that the fahombo stages can be applied as stages of mathematics learning, namely (1) practice solving questions in the easy, medium, and (2) difficult categories, (3) solving questions in the medium and difficult categories, (4) ) completing routine questions and mathematics application questions, and (5) measuring abilities with quizzes.